Identification of Piperlongumine as Potent Inhibitor of Necroptosis - He X; Li M; Ye Z; You X; Wang J; Xiao X; Zhu G; Wei J; Zha Y (Dove Medical Press, 2023)
Xiaoyan He,* Min Li,* Zhi Ye,* Xiaoling You, Jia Wang, Xin Xiao, Guofeng Zhu, Jun Wei, Yunhong Zha Department of Neurology, Institute of Neural Regeneration and Repair, Hubei Clinical Medical Research Center for Rare Disease of Nervous System, The First Hospital of Yichang, Medical College of China Three Gorges University, Yichang, People's Republic of China*These authors contributed equally to this workCorrespondence: Jun Wei; Yunhong Zha, Tel +86-15090922368 ; +86-13872662508, Email junwei@ctgu.edu.cn; yzha7808@ctgu.edu.cnPurpose: Excessive necroptosis contributes to the pathogenesis of several inflammatory and neurodegenerative diseases. Here, using a high-throughput screening approach, we investigated the anti-necroptosis effects of piperlongumine, an alkaloid isolated from the long pepper plant, in vitro and in a mouse model of systemic inflammatory response syndrome (SIRS).Methods: A natural compound library was screened for anti-necroptosis effects in cellular. The underlying mechanism of action of the top candidate piperlongumine was explored by quantifying the necroptosis marker phosphorylated receptor-interacting protein kinase 1 (p-RIPK1) by Western blotting. The anti-inflammatory effect of piperlongumine was assessed in a tumor necrosis factor α (TNFα)-induced SIRS model in mice.Results: Among the compounds investigated, piperlongumine significantly rescued cell viability. The half maximal effective concentration (EC50) of piperlongumine for inhibiting necroptosis was 0.47 μM in HT-29 cells, 6.41 μM in FADD-deficient Jurkat cells, and 2.33 μM in CCRF-CEM cells, while the half maximal inhibitory concentration (IC50) was 95.4 μM in HT-29 cells, 93.02 μM in FADD-deficient Jurkat cells, and 161.1 μM in CCRF-CEM cells. Piperlongumine also significantly inhibited TNFα-induced intracellular RIPK1 Ser166 phosphorylation in cell lines and significantly prevented decreases in body temperature and improved survival in SIRS mice.Conclusion: As a potent necroptosis inhibitor, piperlongumine prevents phosphorylation of RIPK1 at its activation residue Ser166. Piperlongumine thus potently inhibits necroptosis at concentrations safe enough for human cells in vitro and inhibits TNFα-induced SIRS in mice. Piperlongumine has potential clinical translational value for the treatment of the spectrum of diseases associated with necroptosis, including SIRS.Keywords: piperlongumine, natural product, drug repositioning, necroptosis, RIPK1